Pemikiran Ekonomi Umar Chapra - Arifin, Junaidi; Nuryadin, M. Birusman (Rayah Al-Islam, 2024)
Umer Chapra adalah salah seorang ekonom yang menganut mazhab arus utama pemikiran ekonomi Islam kontemporer. Karena keterlibatannya yang luas pada perekonomian bidang ekonomi makro. Chapra, seperti ekonom Muslim lainnya, menekankan betapa pentingnya moral bagi ekonomi yang adil dan sehat. Kemampuan M. Umer Chapra memadukan nilai-nilai Islam dengan konsep ekonomi Barat adalah keahliannya. Sehingga ia bisa disebut sebagai "cendekiawan Islam berprestasi". Gagasannya meliputi konsep Islam tentang negara sejahtera, kebijakan moneter, lembaga keuangan syariah, yang lebih menekankan pada bank sentral dan kebijakannya, serta kesulitan ekonomi yang dihadapi umat Islam. Umer Chapra is one of the economists who adheres to the mainstream school of contemporary Islamic economic thought. Due to his extensive involvement in macroeconomic economics. Chapra, like other Muslim economists, emphasizes the importance of morals for a just and healthy economy. M. Umer Chapra's ability to combine Islamic values with Western economic concepts is his forte. So he can be called an "outstanding Islamic scholar". His ideas include the Islamic concept of the welfare state, monetary policy, Islamic financial institutions, which emphasize central banks and their policies, and the economic difficulties faced by Muslims.